A Kinetic Study of Methane Partial Oxidation over Fe‐ZSM‐5 Using N2O as an Oxidant. Issue 4 (18th January 2018) - Chow, Ying Kit; Dummer, Nicholas F.; Carter, James H.; Meyer, Randall J.; Armstrong, Robert D.; Williams, Christopher; Shaw, Greg; Yacob, Sara; Bhasin, Madan M.; Willock, David J.; Taylor, Stuart H.; Hutchings, Graham J.
Abstract: Catalytic methane oxidation using N2 O was investigated at 300 °C over Fe‐ZSM‐5. This reaction rapidly produces coke (retained organic species), and causes catalyst fouling. The introduction of water into the feed‐stream resulted in a significant decrease in the coke selectivity and an increase in the selectivity to the desired product, methanol, from ca. 1 % up to 16 %. A detailed investigation was carried out to determine the fundamental effect of water on the reaction pathway and catalyst stability. The delplot technique was utilised to identify primary and secondary reaction products. This kinetic study suggests that observed gas phase products (CO, CO2, CH3 OH, C2 H4 and C2 H6 ) form as primary products whilst coke is a secondary product. Dimethyl ether was not detected, however we consider that the formation of C2 products are likely to be due to an initial condensation of methanol within the pores of the zeolite and hence considered pseudo‐primary products. According to a second order delplot analysis, coke is considered a secondary product and its formation correlates with CH3 OH formation. Control experiments in the absence of methane revealed that the rate of N2 O decomposition is similar to that of the full reaction mixture, indicating that the loss of active alpha ‐oxygen sites is the likely cause of the decrease in activity observed and water does not inhibit this process. Abstract : Coke control : Catalytic methane oxidation using N2 O over Fe‐ZSM‐5, in which coke is rapidly produced, was investigated at 300 °C. A significant decrease in coke selectivity and an increase in the selectivity to methanol was achieved by introducing water into the feed‐stream, although catalyst stability was unaffected. Primary and secondary reactions products were identified using the delplot technique.